Clinical outcomes and safety of continuous immunotherapy beyond progression in patients with extensive-stage small cell lung cancer: a retrospective real-world study - Wang, Chengjun; Xuan, Tiantian; Wang, Yanan; Yang, Chuang; Zhao, Wen; Zhang, Rongyu; Meng, Xue; Li, Jisheng (Frontiers in Immunology, 2026)
BackgroundImmunochemotherapy has been approved as first-line treatment for extensive-stage small cell lung cancer. However, second-line treatment options and whether continuous immunotherapy will improve clinical outcome are still controversial. This multi-center retrospective study aimed to investigate the efficacy of continuous immunotherapy for the patients who suffered progression from first-line immunochemotherapy.MethodsWe retrospectively reviewed the medical records of patients with extensive-stage small cell lung cancer treated with first-line immunochemotherapy in three major medical centers in Shandong Province. The patients enrolled achieved disease control during first-line immunochemotherapy but subsequently suffered disease progression.ResultsFrom January 2020 to December 2024, a total of 354 patients treated with first-line immunochemotherapy were enrolled. The first-line progression free survival was 6.60 (95%CI: 6.28-6.92) months. A total of 206 patients were enrolled to compare the efficacy of second-line therapies, including chemotherapy alone (C, 40 cases), chemotherapy + anti-angiogenic therapy (C+A, 17 cases), immunochemotherapy (I+C, 122 cases), immunotherapy + anti-angiogenic therapy (I+A, 11 cases) and immunochemotherapy + anti-angiogenic therapy (I+C+A, 16 cases). Therein, I+C+A group obtained the longest second-line progression free survival of 4.60 (95%CI: 2.71-6.50) months. The second-line progression free survival of I+C group was also longer than that of the C group (3.50, 95%CI: 3.07-3.93 vs 2.33, 95%CI: 1.66-3.01). Regarding overall survival, I+A group achieved the longest overall survival of 22.00 (95%CI: 11.39-32.61) months compared with 19.53 (95%CI: 16.81-22.26) months for I+C group. However, there were no statistical differences in second-line progression free survival and overall survival among the groups. In terms of safety, the rates of adverse events in the I+C and C groups were not statistically significant.ConclusionsContinuous immunotherapy beyond progression in extensive-stage small cell lung cancer shows the trend of prolonging second-line progression free survival, but does not improve the overall survival. Additionally, in the second-line treatment, chemotherapy remains an important cornerstone therapy and anti-angiogenic agent containing strategy may potentially improve survival.